A comprehensive survey of dual-generalized complex Fibonacci and Lucas numbers - Gurses, Nurten; Senturk, Gulsum Yeliz; Yuce, Salim (YILDIZ TECHNICAL UNIV, 2022)
This paper aims to develop dual-generalized complex Fibonacci and Lucas numbers and obtain recurrence relations. Fibonacci and Lucas's approach to dual-generalized complex numbers contains dual-complex, hyper-dual and dual-hyperbolic situations as special cases and allows general contributions to the literature for all real number P. For this purpose, Binet's formulas along with Tagiuri's, Hornsberger's, D'Ocagne's, Cassini's and Catalans identities, are calculated for dual-generalized complex Fibonacci and Lucas numbers. Finally, the results are given, and the special cases for this unification are classified.
Keywords: Dual-generalized complex numbers; Fibonacci numbers; Lucas numbers MSC 2010; 11B39; 11B83; Engineering